Spontaneous Closure of a Fully Developed Macular Hole in a Severely Myopic Eye - C. Bruè; I. Rossiello; J. M. Guidotti; C. Mariotti (Case Reports in Ophthalmological Medicine)
Purpose. Myopic macular holes can be difficult to close with surgery and are frequently associated with retinal detachment. We report on a case of a macular hole in a severely myopic eye that underwent spontaneous closure. Methods. An observational case study. Results. A 55-year-old female was referred to Ophthalmology for a central scotoma and metamorphopsia in the right eye. Visual acuity was 1/20 in both eyes. Fundus examination showed loss of the foveal depression, with a small yellow ring in the center of the fovea in the right eye, and a tilted optic disc and peripapillary staphyloma bilaterally. Spectral domain optical coherence tomography (SD-OCT) revealed a fully developed macular hole with a rim of thickened and slightly elevated retina in the right eye. The patient refused surgery. After 4 years of follow-up, her visual acuity improved to 20/40 in the right eye, and SD-OCT revealed spontaneous sealing of the macular hole without bare retinal pigment epithelium. Conclusions. Myopic macular holes represent a challenge regarding their management, and the prognosis is often poor.